Human cytomegalovirus elicits fetal γδ T cell responses in utero - Vermijlen, David (The Rockefeller University Press, 2010)
The fetus and infant are highly susceptible to viral infections. Several viruses, including human cytomegalovirus (CMV), cause more severe disease in early life compared with later life. It is generally accepted that this is a result of the immaturity of the immune system. γδ T cells are unconventional T cells that can react rapidly upon activation and show major histocompatibility complex–unrestricted activity. We show that upon CMV infection in utero, fetal γδ T cells expand and become differentiated. The expansion was restricted to Vγ9-negative γδ T cells, irrespective of their Vδ chain expression. Differentiated γδ T cells expressed high levels of IFN-γ, transcription factors T-bet and eomes, natural killer receptors, and cytotoxic mediators. CMV infection induced a striking enrichment of a public Vγ8Vδ1-TCR, containing the germline-encoded complementary-determining-region-3 (CDR3) δ1–CALGELGDDKLIF/CDR3γ8–CATWDTTGWFKIF. Public Vγ8Vδ1-TCR–expressing cell clones produced IFN-γ upon coincubation with CMV-infected target cells in a TCR/CD3-dependent manner and showed antiviral activity. Differentiated γδ T cells and public Vγ8Vδ1-TCR were detected as early as after 21 wk of gestation. Our results indicate that functional fetal γδ T cell responses can be generated during development in utero and suggest that this T cell subset could participate in antiviral defense in early life.